2004
DOI: 10.1073/pnas.0402625101
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic processivity of the T4 DNA polymerase during replication

Abstract: The polymerase (gp43) processivity during T4 replisome mediated DNA replication has been investigated. The size of the Okazaki fragments remains constant over a wide range of polymerase concentrations. A dissociation rate constant of Ϸ0.0013 sec ؊1 was measured for the polymerases from both strands, consistent with highly processive replication on both the leading and lagging strands. This processive replication, however, can be disrupted by a catalytically inactive mutant D408N gp43 that retains normal affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
125
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 28 publications
9
125
2
4
Order By: Relevance
“…Previously, an active exchange process was observed for the T4 Pol holoenzyme (9). To test whether a similar Pol exchange occurs for yeast Pol␦ we constructed a Pol␦ trap (Pol␦ AA ) by mutating the two active-site aspartates of the catalytic subunit of Pol␦ to alanine (Pol3 D762A, D764A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, an active exchange process was observed for the T4 Pol holoenzyme (9). To test whether a similar Pol exchange occurs for yeast Pol␦ we constructed a Pol␦ trap (Pol␦ AA ) by mutating the two active-site aspartates of the catalytic subunit of Pol␦ to alanine (Pol3 D762A, D764A).…”
Section: Resultsmentioning
confidence: 99%
“…Using a catalytically impaired T4 replicative Pol (gp43) trap, it was found that gp43 from solution undergoes active exchange with gp43 in the holoenzyme (9). A model was proposed to explain the Pol exchange process in T4 phage based on known x-ray crystal structures of both gp43 and gp45.…”
mentioning
confidence: 99%
“…These reactions occur with high fidelity (1,4). Polymerases also achieve high processivity on leading and lagging strands, despite differences in rate for individual substrates/ templates (5). The mechanism of enzymatic primer extension is complex.…”
mentioning
confidence: 99%
“…It is well established that lagging strand components, other than the polymerase, are recruited continuously from solution. The current study by Yang et al (2) shows that the polymerase is exchangeable within the replisome complex but only rarely leaves the complex if a replacement polymerase is not available. The helicase appears to be the most solidly fixed component and has been suggested to be the ''cornerstone'' of the replisome (1).…”
Section: Dynamic Processivitymentioning
confidence: 99%
“…The most obvious is in replication past a blocking lesion on the template. The exchange mechanism proposed by Yang et al (2) provides a means of transferring the primer terminus from a stalled replicative polymerase to a specialized lesion bypass polymerase. One can envisage a straightforward targeting process.…”
Section: Biological Implicationsmentioning
confidence: 99%